Patient satisfaction with the quality of nursing care in critical care units and medical wards in West Bank Hospitals, Palestine: A cross-sectional study - Hiba Smerat; Moath Abu Ejheisheh; Ahmad Ayed; Ibrahim Aqtam; Ahmad Batran (PLoS ONE, 2025)
Introduction Patient satisfaction with nursing care is a crucial indicator of healthcare quality, influencing patient outcomes and experiences. In the West Bank, Palestine, understanding patient satisfaction is essential for improving healthcare services, particularly in resource-limited settings. This study aimed to evaluate patient satisfaction with nursing care in intensive care units (ICUs), coronary care units (CCUs), and medical wards within both governmental and non-governmental hospitals in the region, aligning with the revised study focus. Methods A descriptive cross-sectional study was conducted in four hospitals in the West Bank, Palestine, over a three-month period (June–August 2024), involving 201 hospitalized patients selected through convenience sampling. Data were collected using the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ), a validated tool assessing multiple dimensions of nursing care. Descriptive statistics, independent t-tests, one-way ANOVA, and multiple linear regression analyses were conducted to identify predictors of patient satisfaction. Results Participants’ ages ranged from 21 to 84 years (M = 38.39, SD = 14.16), with 50.7% female participants. The mean overall satisfaction score was M = 64.50 (SD = 14.16), indicating moderate satisfaction. A significant difference in satisfaction levels was found between ICU and medical ward patients (t = 2.45, p = 0.015), with ICU patients reporting higher satisfaction. Regression analysis identified age (B = 0.162, p = 0.005) and health status (B = 0.242, p = 0.001) as significant predictors of satisfaction, with older and healthier patients reporting higher satisfaction levels. Additionally, frequent hospitalizations were negatively associated with satisfaction (B = -0.107, p = 0.022). Perceived confidence in responding to deteriorating conditions significantly influenced overall perception (r = 0.342, p < 0.01). Conclusion Moderate patient satisfaction highlights the need for targeted interventions to enhance nurse-patient communication and family involvement, particularly for younger and frequently hospitalized patients. Hospitals should implement specialized training programs to improve communication and patient engagement. Policy interventions should focus on strengthening patient-centered nursing care in both governmental and non-governmental hospitals in the West Bank.